A Case of Chronic Ectopic Pregnancy Mimicking Pelvic Malignancy - Mine Kanat Pektaş; Ömer Lütfi Tapısız; Tayfun Güngör (Medical Network, 2009)
A case of chronic ectopic pregnancy mimicking pelvic malignancy is presented, indicating significance of ectopic pregnancy in discrimination of pelvic masses. A heterogenous solid mass measuring 72x50x44 mm was sonographically visualized in the right adnexal area of a 24-year-old primiparous woman presenting with six-week-long intermittent pelvic pain and irregular vaginal bleeding. Betahuman chorionic gonadotropin (hCG) and CA 125 levels were respectively 6.02 IU/ml and 205.4 U/ml. Right salpingoopherectomy was done and histopathologic examination revealed ectopic pregnancy. Chronic ectopic pregnancy usually presents with prolonged clinical symptoms which are often misleading. Although the adjoint use of sonography and beta-hCG assay increases dianostic accuracy, a negative beta-hCG value does not rule out chronic ectopic pregnancy. Increased awareness of chronic ectopic pregnancy allows its preoperative diagnosis and prompt treatment.